Multi-omics analysis reveals indicator features of microbe-host interactions during Candida albicans colonization and subsequent infection - Zhang, Huan; Song, Daoyuan; Luo, Qiulin; Yu, Jiangkun; Wei, Yingpu; Chen, Di; Wu, Guangjuan; Zhang, Zhi; Li, Zhao; Jiang, Hongchao; Gan, Jingquan; Deng, Deyao; et al. (Frontiers in Microbiology, 2024)
IntroductionCandida albicans gastrointestinal (GI) colonization is crucial for the onset of invasive disease. This research encompassed 31 patients diagnosed with Candida spp. bloodstream infections during their admission to a university hospital in China.MethodsWe explored risk factors associated with C. albicans GI colonization and ensuing translocated infection. Animal models were established via gavage with clinical isolates of C. albicans to induce GI tract colonization and subsequent kidney translocation infection. Our analysis is focused on 16S rRNA gene sequencing, metabolomics of colon contents, and transcriptomics of colon tissues, examining the intestinal barrier, inflammatory responses, and immune cell infiltration.ResultsThis study observed that down-regulation of programmed cell death 1 (PD-1) in colon tissues is likely linked to the progression from C. albicans colonization to translocated infection. Notably, reductions in Dubosiella abundance and Short-chain fatty acids (SCFA) levels, coupled with increases in Mucispirillum and D-erythro-imidazolylglycerol phosphate, were indicator features during the advancement to translocated invasive infection in hosts with rectal colonization by C. albicans and lower serum protein levels.ConclusionGiven the similarity in intestinal bacterial communities and metabolome profiles, antifungal treatment may not be necessary for patients with nonpathogenic C. albicans colonization. The reduced expression of PD-1 in colon tissues may contribute to the transition from colonized C. albicans to subsequent translocated infection. The indicator features of decreased Dubosiella abundance and SCFA levels, coupled with increased Mucispirillum and D-erythro-imidazolylglycerol phosphate, are likely linked to the development of translocated invasive infection in hosts colonized rectally by C. albicans with lower serum protein levels.ImportanceCandida albicans invasive infections pose a significant challenge to contemporary medicine, with mortality rates from such fungal infections remaining high despite antifungal treatment. Gastrointestinal colonization by potential pathogens is a critical precursor to the development of translocated infections. Consequently, there is an increasing demand to identify clinical risk factors, multi-omics profiles, and key indicators to prevent the progression to translocated invasive infections in patients colonized rectally by C. albicans.